Relationship between physical activity and comprehensive development in early childhood education according to teachers' perceptions - Lady Briggith Gil-Sagastegui; Mayte Sandoval-Lavado; Maricielo Aylin Ciudad-Mozo; Soveida Haraminda Lalangui Neyra (TUMI Health Sciences Research, 2026)
Background: Physical activity during early childhood is an important component of healthy growth and may contribute to motor, cognitive, social, and emotional development. Understanding its relationship with children’s holistic development may support educational practices aimed at promoting well-being from the preschool stage. Objective: To determine the association between physical activity and holistic development in preschool children according to teachers’ perceptions. Methods: An observational, analytical, cross-sectional study with a quantitative approach was conducted. The entire accessible population of 50 preschool children aged 3 to 5 years was included using a census approach. Teachers assessed physical activity and holistic development using structured questionnaires with evidence of content validity and adequate internal consistency. Categorical variables were summarized using frequencies and percentages, and the association between the study variables was evaluated using the chi-square test, with statistical significance set at p < 0.05. Results: Physical activity was classified as fair in 46.0% of children, good in 46.0%, poor in 6.0%, and excellent in 2.0%. Holistic development was predominantly moderate (70.0%), followed by high (26.0%) and low (4.0%) levels. No statistically significant association was found between physical activity and holistic development (p = 0.070). Conclusions: Physical activity and holistic development were not significantly associated according to teachers’ perceptions. Nevertheless, both represent relevant components of preschool development and should be considered within comprehensive educational strategies for early childhood.